Tetralogy of Fallot in an Alaskan malamute: a case report - Sarikan , Sitha (Journal of Mahanakorn Veterinary Medicine, 2024)
A 3-month-old female Alaskan malamute was presented with a grade IV/VI systolic heart murmur, exercise intolerance, and anorexia. On examination, the dog was found to have cyanosis and inadequate growth. Echocardiography revealed a dextroposition of the aorta, a large ventricular septal defect, severe pulmonic stenosis (maximal velocity 4.77 m/s), and right ventricular hypertrophy. The dog was diagnosed with tetralogy of Fallot (TOF) and managed medically with atenolol 0.3 mg/kg SID. The incidence of TOF in dogs has been reported to be approximately 0.6 - 1%. This report is the first to encompass a complete blood count, thoracic radiographs, and echocardiography findings in an Alaskan malamute diagnosed with TOF in Thailand.